Dickinson's daisy/sun(set), Daoism, and Emerson. Issue 1 (21st April 2021) - Kang, Yanbin
Abstract: Regarding "The Daisy follows soft the Sun -" (Fr161), the interpretive energy has been invested upon formulating the love relationship between the daisy and the sun, describing her humbleness, faithfulness, and masochistic attachment, her transformation from subservience to assertiveness or her assertion in disguise of humility. From a combined perspective of Daoism and Ralph Waldo Emerson, this essay argues that this poem features the course of nature, the transcendent moment that gravitates within, and an impersonal love. The poem dramatizes a process of returning to quietude characterized by stillness, darkness, and serenity. The Emersonian vein is clearly evidenced in the daisy's posture of "[Sitting] shyly" at night, returning to solitude, and finding a rest within an edifying sentiment. The daisy-sunset love echoes Emerson's spiritual love which presupposes a non-possessive attitude. This strand of theme intersects with softening the light, an idea which is essential for a flourishing state of being and interaction.